Corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln and preparation method of corrosion-resistant silicon-aluminum refractory material
By adding corrosion-resistant microcapsules, hafnium nitride and modified glaze to the silicon-aluminum refractory materials, and using a multi-layer structure preparation method, the problem of silicon-aluminum refractory materials being easily corroded in hazardous waste rotary kilns is solved, and its corrosion resistance and thermal stability are significantly improved.
Patent Information
- Application Number
- CN202411865759.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-29
AI Technical Summary
Existing silicon-aluminum-based refractory materials are susceptible to alkali metal corrosion in hazardous waste rotary kilns, resulting in structural damage and degradation of performance.
A corrosion-resistant silicon-aluminum refractory material was designed, and corrosion-resistant microcapsules, hafnium nitride and modified glaze were added, and a multi-layer structure preparation method was adopted to improve the corrosion resistance and thermal stability of the material.
It significantly improves the corrosion resistance and thermal stability of refractory materials, extends its service life in high temperature environments, and reduces the speed of corrosion process.
Smart Images

Figure CN119899022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kilns and a preparation method thereof. Background Art
[0002] Hazardous waste rotary kiln can dispose of organic vapor, high-concentration organic waste liquid, liquid organic waste, granular uniform waste, non-uniform loose waste, low melting point waste, organic waste containing flammable components, untreated coarse and bulk waste, halogenated aromatic waste, organic sludge, etc. It can also be used for drying and incineration of municipal sludge, aeration tank biochemical sludge, printing and dyeing, pesticides, and chemical waste / sludge.
[0003] The main factors that damage refractory materials are thermal stress damage, mechanical wear and corrosion damage, among which the damage caused by alkali metal corrosion accounts for more than 40% of all damage. The main reason why aluminum-silicon refractory materials are damaged by alkali corrosion is that the alkali metal reacts with the refractory materials at high temperatures, and the volume expands while generating new phases, forming internal stress inside. At the same time, the properties of the new substances generated are different from those of the surrounding original substances. When the temperature and other environmental conditions change, they are easily separated from the surrounding substances, causing the material to become loose in structure, cracked, or even peeled off on a large scale.
[0004] In order to solve the above problems, the present invention decides to design a corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln and a preparation method thereof. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln and a preparation method thereof.
[0006] A corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln, comprising the following components by mass percentage:
[0007] Silicon dioxide: 8-10%;
[0008] Alumina: 5-7%;
[0009] Mullite: 20-30%;
[0010] Hafnium nitride: 0.3-0.5%;
[0011] Corrosion-resistant microcapsules: 0.1-0.3%;
[0012] Binder: 3-5%;
[0013] Corundum: remainder.
[0014] Furthermore, the preparation method of the corrosion-resistant microcapsules is:
[0015] Dispersing polyvinyl alcohol and pentaerythritol in deionized water at a mass ratio of 1:0.5:40-50, and adjusting the pH to 7-9 to obtain an aqueous phase solution; mixing and ultrasonically dispersing the modified glaze, aluminum oxide powder with a particle size of ≤2 μm, an emulsifier, and aluminum dihydrogen phosphate solution with a mass concentration of 40-50% at a mass ratio of 1:1.5:0.2-0.8:0.5 to obtain an oil phase solution;
[0016] The oil phase solution and the water phase solution are mixed and emulsified in a mass ratio of 2 to 3:7, the mixing speed is 4000 to 5000 r / min, the heating temperature is 25 to 45° C., and the emulsification time is 10 to 15 minutes to obtain an emulsion; flame-retardant viscose fibers are added to the emulsion in a mass ratio of 1:0.02 to 0.04, the temperature is raised to 65 to 75° C. in a nitrogen atmosphere, and the mixture is stirred for 2 to 3 hours, and then vacuum dried at -15 to -5° C. for 10 to 12 hours to obtain corrosion-resistant microcapsules with a particle size of 25 to 45 μm.
[0017] Description: Modified glaze and alumina powder and other ingredients have good chemical stability. When wrapped in microcapsules, they can better exert their corrosion resistance, making it difficult for refractory materials to undergo chemical reactions when in contact with corrosive media such as acids and alkalis, thereby improving the corrosion resistance of refractory materials; ingredients such as polyvinyl alcohol and emulsifiers can reduce the viscosity of oil phase solution and water phase solution, making it easier for the two to mix and emulsify to form a uniform and stable emulsion, thereby ensuring the consistency of the quality and performance of the microcapsules; aluminum dihydrogen phosphate solution is used as a binder to make the material structure denser, reduce the channels for corrosive substances to invade, and thereby improve the corrosion resistance of refractory materials.
[0018] Furthermore, the preparation method of the modified glaze is:
[0019] The glaze and 1-naphthalenecarboxylic acid are ultrasonically dispersed in methanol at a mass ratio of 4:1:20-25, and then centrifugally washed and dried to obtain a modified glaze intermediate;
[0020] After the modified glaze intermediate is plasma cleaned, a TiC film is magnetron sputtered on the surface of the modified glaze intermediate, argon is used as the protective gas, nitrogen is used as the reaction gas, the coating working pressure is 0.6-0.8 Pa, the titanium target sputtering power is 120-180 W, the argon flow rate is 32-38 mL / min, the nitrogen flow rate is 1.5-2.5 mL / min, the sputtering temperature is 420-480° C., and the magnetron sputtering coating treatment time is 40-50 min to obtain a modified glaze.
[0021] Description: 1-Naphthalenecarboxylic acid has certain chemical stability and antioxidant properties. After being mixed with glaze and subjected to subsequent treatment, it can work together with titanium carbide film to enhance the corrosion resistance of the modified glaze and further improve the stability of refractory materials in harsh environments; plasma cleaning can remove impurities and pollutants on the surface of the glaze, and at the same time activate its surface to increase surface energy and make its surface rougher, thereby enhancing the mechanical bonding force with the refractory material; the glaze itself also has certain high temperature resistance. After modification, it cooperates with titanium carbide to better resist the damage of high temperature to the refractory material and improve the high temperature resistance limit of the refractory material.
[0022] Furthermore, the glaze is selected from any one of zircon powder, kyanite powder and feldspar powder.
[0023] Description: Zircon powder can significantly improve the bonding performance of body and glaze, increase the hardness of refractory materials, and enhance the high temperature resistance and wear resistance of refractory materials. Kyanite powder can effectively compensate for the shrinkage of materials at high temperatures, reduce the generation of cracks, and improve the volume stability and service life of materials. Feldspar powder can be used as a flux to reduce the sintering temperature of materials, promote the densification of materials, and improve the mechanical strength and refractory performance of materials.
[0024] Furthermore, the power of the plasma cleaning is 350-450W, and the cleaning time is 5-10 minutes.
[0025] Note: When the power is too low, the active particles in the plasma cannot be fully excited, making it difficult to form sufficient active groups and chemical bonds on the surface of the workpiece, resulting in an insufficient bond between the film layer and the substrate; too high a power will weaken the mechanical properties and corrosion resistance of the workpiece.
[0026] Furthermore, the emulsifier is Span80.
[0027] Description: Span80 can provide good emulsification effect and maintain the stability of the emulsion, which is not easy to separate or precipitate.
[0028] Furthermore, the binder includes any one or more of cement, silicate and aluminate.
[0029] Description: The above binders can improve the strength and stability of refractory materials and resist corrosion from chemical substances such as acids, alkalis, and salts.
[0030] Furthermore, the particle size of the silicon dioxide is 40-70 nm, the particle size of the aluminum oxide is ≤5 mm, the particle size of the mullite is 1-3 mm, and the particle size of the corundum includes three types of 1-3 mm, 0.088-1 mm, and 0-0.088 mm with a mass ratio of 1:1.5-2:1.5.
[0031] Description: Silica particles are smaller in size and can be filled into the gaps between other larger particles, making the structure of the refractory material denser, increasing its volume density and strength, reducing porosity, and thus enhancing the corrosion resistance and wear resistance of the refractory material; large particles of corundum can provide the main skeleton support, enhancing the overall strength and stability of the refractory material; medium particles of corundum can fill the gaps between large particles, further improving the density of the structure; small particles of corundum can be filled into smaller pores, making the microstructure of the refractory material more uniform and compact, thereby significantly improving the strength, density, corrosion resistance and other properties of the refractory material.
[0032] The method for preparing a corrosion-resistant silicon-aluminum refractory material for a hazardous waste rotary kiln as described in any one of the above comprises the following steps:
[0033] S1. Mix silicon dioxide, aluminum oxide, mullite and corundum uniformly and divide them into mixture A and mixture B with a mass ratio of 1 to 3:1; first, stir and mix mixture A and corrosion-resistant microcapsules in a nitrogen atmosphere for 20 to 30 minutes, with a nitrogen introduction rate of 0.1 to 0.3 L / min, to obtain a first mixture;
[0034] S2, stirring and mixing the mixture B and hafnium nitride under the action of microwave, the microwave power is 400-600W, the time is 5-10min, to obtain a second mixture;
[0035] S3, stirring and mixing the first mixed material obtained in step S1, the second mixed material obtained in step S2, and the binder for 15 to 25 minutes to obtain a third mixed material;
[0036] S4, 15-20% of the third mixture obtained in step S3 is used as W1, and pre-pressed at 120-130 MPa as the center layer, and the remaining third mixture is divided into n portions, and the mass of each portion of the third mixture is W n , then W n =2~2.5W n-1 , n>1, n portions of the third mixed material are used to wrap the previous layer in turn, and then pre-pressed at 120-130 MPa to obtain a new layer, and the length, width and height ratios of each layer are equal to obtain a blank;
[0037] S5. The blank of step S4 is then fired at a high temperature of 1250-1350° C. for 10-12 hours to obtain a silicon-aluminum refractory material.
[0038] Compared with the existing silicon-aluminum refractory materials, the present invention has the following beneficial effects:
[0039] (1) The corrosion-resistant microcapsules added to the refractory material prepared by the present invention can block the transfer of heat to a certain extent, reduce the conduction of heat into the interior of the material, reduce the temperature rise rate inside the refractory material, help maintain the structural integrity and performance stability of the material, and extend its service life in a high-temperature environment. The modified glaze and alumina powder and other components in the corrosion-resistant microcapsules themselves have good chemical stability. Under the wrapping of the microcapsules, they can better exert their corrosion resistance, making it difficult for the refractory material to undergo chemical reactions when it contacts corrosive media such as acids and alkalis, thereby improving the corrosion resistance of the refractory material.
[0040] (2) Hafnium nitride is added to the refractory material prepared by the present invention. Hafnium nitride has strong chemical stability and is not easy to react with chemical substances such as acids, alkalis, and salts. In harsh chemical environments, it can maintain the structure and performance of the refractory material stable, thereby improving its corrosion resistance. In addition, hafnium nitride has a relatively low thermal expansion coefficient. When combined with other materials, it can reduce the overall thermal expansion rate of the refractory material and improve its thermal shock stability. It makes the refractory material less likely to crack and be damaged under conditions of rapid temperature changes, thereby ensuring its structural integrity during heating and cooling.
[0041] (3) When preparing refractory materials, the present invention divides the refractory materials into a multi-layer structure that is coated sequentially from the inside to the outside, so that the particle distribution inside the material is more uniform and the density difference of each part is reduced, which helps to improve the overall strength and stability of the refractory materials, reduce stress concentration and crack generation caused by uneven density, and thus extend its service life; as the mixed material layers are wrapped sequentially, each layer can serve as a protective barrier for the internal material, increasing the difficulty and path length for corrosive media such as slag and gas to reach the core layer; the outer layer material first contacts the corrosive medium, which can consume or block the corrosion effect to a certain extent, delaying the corrosion process, thereby improving the overall corrosion resistance of the refractory material, so that it can maintain good stability in harsh chemical environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a comparison chart of the corrosion rate results of Experimental Example 1 of the present invention;
[0043] Figure 2 is a comparison chart of the thermal shock resistance results of Experimental Example 1 of the present invention;
[0044] Figure 3 is a comparison chart of the corrosion rate results of Experimental Example 2 of the present invention;
[0045] Figure 4 is a comparison chart of the thermal shock resistance results of Experimental Example 2 of the present invention;
[0046] Figure 5 is a comparison chart of the corrosion rate results of Experimental Example 3 of the present invention;
[0047] Figure 6 It is a comparison chart of the thermal shock resistance results of Experimental Example 3 of the present invention. DETAILED DESCRIPTION
[0048] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0049] Example 1: A corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln, comprising the following components by mass percentage:
[0050] Silicon dioxide: 9%;
[0051] Alumina: 6%;
[0052] Mullite: 25%;
[0053] Hafnium nitride: 0.4%;
[0054] Corrosion-resistant microcapsules: 0.2%;
[0055] Cement: 4%;
[0056] Corundum: remainder;
[0057] The particle size of the silicon dioxide is 40-70 nm, the particle size of the aluminum oxide is ≤5 mm, the particle size of the mullite is 1-3 mm, and the particle size of the corundum includes three types of 1-3 mm, 0.088-1 mm, and 0-0.088 mm with a mass ratio of 1:1.8:1.5;
[0058] The preparation method of the corrosion-resistant microcapsules is:
[0059] Dispersing polyvinyl alcohol and pentaerythritol in deionized water at a mass ratio of 1:0.5:45, and adjusting the pH to 8 to obtain an aqueous phase solution; mixing the modified glaze, alumina powder with a particle size of 1 to 2 μm, Span80, and aluminum dihydrogen phosphate solution with a mass concentration of 45% at a mass ratio of 1:1.5:0.5:0.5, and ultrasonically dispersing to obtain an oil phase solution;
[0060] The oil phase solution and the water phase solution are mixed and emulsified at a mass ratio of 2.5:7, the mixing speed is 4500 r / min, the heating temperature is 32° C., and the emulsification time is 12 min to obtain an emulsion; flame-retardant viscose fiber is added to the emulsion at a mass ratio of 1:0.03, the temperature is raised to 70° C. in a nitrogen atmosphere, and stirred for 2.5 hours, and then vacuum dried at -10° C. for 11 hours to obtain corrosion-resistant microcapsules with a particle size of 32 to 38 μm;
[0061] The preparation method of the modified glaze is:
[0062] The glaze and 1-naphthalenecarboxylic acid are ultrasonically dispersed in methanol at a mass ratio of 4:1:22.5, and then centrifugally washed and dried to obtain a modified glaze intermediate; the glaze is zircon powder; the centrifugal speed is 3000 rpm, the washing is washed with deionized water for 3 times, and the drying temperature is 150°C;
[0063] After the modified glaze intermediate is plasma cleaned, the plasma cleaning power is 400 W, the cleaning time is 8 minutes, and then a TiC film is magnetron sputtered on the surface of the modified glaze intermediate, argon is used as the protective gas, nitrogen is used as the reaction gas, the coating working pressure is 0.7 Pa, the titanium target sputtering power is 150 W, the argon flow rate is 35 mL / min, the nitrogen flow rate is 2 mL / min, the sputtering temperature is 450° C., and the magnetron sputtering coating treatment time is 45 minutes to obtain a modified glaze.
[0064] Example 2: A method for preparing a corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln as described in Example 1, comprising the following steps:
[0065] S1. Mix silica, alumina, mullite and corundum evenly and divide them into mixture A and mixture B with a mass ratio of 2:1; first, stir and mix mixture A and corrosion-resistant microcapsules under a nitrogen atmosphere for 25 minutes with a nitrogen introduction rate of 0.2 L / min to obtain a first mixture;
[0066] S2, stirring and mixing the mixture B and hafnium nitride under the action of microwave, the microwave power is 500 W, the time is 5 minutes, to obtain a second mixture;
[0067] S3, stirring and mixing the first mixture obtained in step S1, the second mixture obtained in step S2 and the binder for 20 minutes to obtain a third mixture; the stirring speed of steps S1, S2 and S3 is 600 rpm;
[0068] S4, 18% of the third mixture obtained in step S3 is used as W1, and pre-pressed at 125 MPa as the center layer, and the remaining third mixture is divided into n portions, and the mass of each portion of the third mixture is W n , then W n =2.2W n-1 , n>1, n portions of the third mixed material are used to wrap the previous layer in turn, and then pre-pressed at 125 MPa to obtain a new layer, and the length, width and height ratios of each layer are equal to obtain a blank;
[0069] S5. The blank of step S4 is then fired at 1300° C. for 11 hours to obtain a silicon-aluminum refractory material.
[0070] Example 3: This example is different from Example 1 in that, by mass percentage, it includes the following components: silicon dioxide: 8%; aluminum oxide: 5%; mullite: 20%; hafnium nitride: 0.3%; corrosion-resistant microcapsules: 0.3%; silicate: 3%; corundum: balance; the particle size of the silicon dioxide is 40-50nm, the particle size of the aluminum oxide is ≤5mm, the particle size of the mullite is 1-3mm, and the particle size of the corundum includes three types of 1-3mm, 0.088-1mm, and 0-0.088mm in a mass ratio of 1:1.5:1.5
[0071] Example 4: This example is different from Example 1 in that, in terms of mass percentage, it includes the following components: silicon dioxide: 10%; aluminum oxide: 7%; mullite: 30%; hafnium nitride: 0.5%; corrosion-resistant microcapsules: 0.1%; aluminate: 5%; corundum: balance; the particle size of the silicon dioxide is 60-70nm, the particle size of the aluminum oxide is ≤5mm, the particle size of the mullite is 1-3mm, and the particle size of the corundum includes three types of 1-3mm, 0.088-1mm, and 0-0.088mm in a mass ratio of 1:2:1.5.
[0072] Example 5: This example is different from Example 1 in that polyvinyl alcohol and pentaerythritol are dispersed in deionized water at a mass ratio of 1:0.5:40, and the pH is adjusted to 7 to obtain an aqueous solution.
[0073] Example 6: This example is different from Example 1 in that polyvinyl alcohol and pentaerythritol are dispersed in deionized water at a mass ratio of 1:0.5:50, and the pH is adjusted to 9 to obtain an aqueous solution.
[0074] Example 7: This example is different from Example 1 in that the modified glaze, alumina powder, Span80 and 40% aluminum dihydrogen phosphate solution are mixed and ultrasonically dispersed in a mass ratio of 1:1.5:0.2:0.5 to obtain an oil phase solution.
[0075] Example 8: This example is different from Example 1 in that the modified glaze, alumina powder, Span80 and 50% aluminum dihydrogen phosphate solution are mixed and ultrasonically dispersed in a mass ratio of 1:1.5:0.8:0.5 to obtain an oil phase solution.
[0076] Example 9: This example is different from Example 1 in that the oil phase solution and the water phase solution are mixed and emulsified in a mass ratio of 2:7, the mixing speed is 4000 r / min, the heating temperature is 25°C, and the emulsification time is 10 min.
[0077] Example 10: This example is different from Example 1 in that the oil phase solution and the water phase solution are mixed and emulsified in a mass ratio of 3:7, the mixing speed is 5000 r / min, the heating temperature is 45°C, and the emulsification time is 15 min.
[0078] Example 11: This example is different from Example 1 in that flame-retardant viscose fiber is added to the emulsion at a mass ratio of 1:0.02, and the temperature is raised to 65° C. and stirred for 2 hours under a nitrogen atmosphere.
[0079] Example 12: This example is different from Example 1 in that flame-retardant viscose fiber is added to the emulsion at a mass ratio of 1:0.04, and the temperature is raised to 75° C. and stirred for 3 hours under a nitrogen atmosphere.
[0080] Example 13: This example is different from Example 1 in that the corrosion-resistant microcapsules with a particle size of 25 to 32 μm are obtained by vacuum drying at -15°C for 10 h.
[0081] Example 14: This example is different from Example 1 in that the corrosion-resistant microcapsules with a particle size of 38 to 45 μm are obtained by vacuum drying at -5°C for 12 hours.
[0082] Example 15: This example is different from Example 1 in that kyanite powder and 1-naphthalenecarboxylic acid are ultrasonically dispersed in methanol at a mass ratio of 4:1:20.
[0083] Example 16: This example is different from Example 1 in that potassium feldspar powder and 1-naphthalenecarboxylic acid are ultrasonically dispersed in methanol at a mass ratio of 4:1:25.
[0084] Example 17: The difference between this example and Example 1 is that the plasma cleaning power is 350 W and the cleaning time is 5 minutes.
[0085] Example 18: The difference between this example and Example 1 is that the plasma cleaning power is 450 W and the cleaning time is 10 min.
[0086] Example 19: The difference between this example and Example 1 is that the coating working gas pressure is 0.6 Pa, the titanium target sputtering power is 120 W, the argon flow rate is 32 mL / min, the nitrogen flow rate is 1.5 mL / min, the sputtering temperature is 420°C, and the magnetron sputtering coating treatment time is 40 min.
[0087] Example 20: The difference between this example and Example 1 is that the coating working gas pressure is 0.8 Pa, the titanium target sputtering power is 180 W, the argon flow rate is 38 mL / min, the nitrogen flow rate is 2.5 mL / min, the sputtering temperature is 480°C, and the magnetron sputtering coating treatment time is 50 min.
[0088] Example 21: This example is different from Example 2 in that silicon dioxide, aluminum oxide, mullite and corundum are mixed to obtain a mixture A and a mixture B in a mass ratio of 1:1.
[0089] Example 22: This example is different from Example 2 in that silicon dioxide, aluminum oxide, mullite and corundum are mixed to obtain mixture A and mixture B in a mass ratio of 3:1.
[0090] Example 23: This example is different from Example 2 in that the mixture A and the corrosion-resistant microcapsules are stirred and mixed under a nitrogen atmosphere for 20 minutes, and the nitrogen introduction rate is 0.1 L / min.
[0091] Example 24: This example is different from Example 2 in that the mixture A and the corrosion-resistant microcapsules are stirred and mixed under a nitrogen atmosphere for 30 minutes, and the nitrogen introduction rate is 0.3 L / min.
[0092] Example 25: This example is different from Example 2 in that the mixture B and hafnium nitride are stirred and mixed under the action of microwaves with a microwave power of 400 W and a time of 5 min.
[0093] Example 26: This example is different from Example 2 in that the mixture B and hafnium nitride are stirred and mixed under the action of microwaves with a microwave power of 600 W and a time of 10 min.
[0094] Example 27: This example is different from Example 2 in that the first mixture obtained in step S1, the second mixture obtained in step S2 and the binder are stirred and mixed for 15 minutes, and 15% of the third mixture obtained in step S3 is taken as W1 and pre-pressed at 120 MPa as the center layer.
[0095] Example 28: This example is different from Example 2 in that the first mixture obtained in step S1, the second mixture obtained in step S2 and the binder are stirred and mixed for 25 minutes, and 20% of the third mixture obtained in step S3 is taken as W1 and pre-pressed at 130 MPa as the center layer.
[0096] Embodiment 29: This embodiment differs from Embodiment 2 in that W n =2W n-1 , and then pre-pressed at 120MPa.
[0097] Embodiment 30: This embodiment differs from Embodiment 2 in that W n =2.5W n-1 , and then pre-pressed at 130MPa.
[0098] Example 31: This example is different from Example 2 in that the blank of step S4 is fired at a high temperature of 1250°C for 10 hours.
[0099] Example 32: This example is different from Example 2 in that the blank of step S4 is fired at a high temperature of 1350°C for 12 hours.
[0100] Experimental Example: The description of this experimental example is based on the scheme described in Example 2, and is intended to illustrate the practical application effect of the present invention.
[0101] The corrosion resistance and thermal stability of the refractory materials of various embodiments were tested. Each embodiment was tested three times, and the average results of the three corrosion rate % and thermal shock resistance % were taken as the final result.
[0102] 1. To explore the influence of the proportion of alumina and the preparation parameters of corrosion-resistant microcapsules on the corrosion rate and thermal shock resistance of refractory materials.
[0103] The difference between Control Example 1 and Example 1 is that no flame retardant viscose fiber is added when preparing the corrosion-resistant microcapsules;
[0104] Depend on Figure 1 and Figure 2 The results show that flame-retardant viscose fiber can resist the chemical reaction of some corrosive media at high temperatures. When the material is subjected to thermal shock, the flame-retardant viscose can absorb and disperse part of the energy, reduce the generation and expansion of cracks, and improve the thermal shock resistance of the material. Therefore, when the flame-retardant viscose fiber is missing in the control example 1, the corrosion rate of the refractory material is significantly increased and the thermal shock resistance is significantly reduced.
[0105] By comparing Examples 1 and 3 to 14, it can be seen that too small or too large alumina proportion, too small or too large polyvinyl alcohol proportion, too small or too large modified glaze proportion, too small or too large emulsification parameters, too small or too large flame retardant viscose fiber addition parameters and too small or too large vacuum drying parameters will lead to an increase in the corrosion rate of the refractory material and a decrease in thermal shock resistance. Therefore, in comprehensive comparison, the parameter effect of Example 1 is relatively better.
[0106] 2. Investigate the effects of preparation parameters of modified glazes on the corrosion rate and thermal shock resistance of refractory materials.
[0107] The difference between Comparative Example 2 and Example 1 is that magnetron sputtering coating is not performed when preparing the modified glaze;
[0108] Depend on Figure 3 and Figure 4 The results show that magnetron sputtering coating can cooperate with glaze to better resist the damage of high temperature to refractory materials. Therefore, in comparative example 2, which lacks the modification of glaze by magnetron sputtering coating, the corrosion rate of refractory materials is significantly increased and the thermal shock resistance is significantly decreased.
[0109] By comparing Examples 1 and 15 to 20, it can be seen that too small or too large a proportion of 1-naphthalenecarboxylic acid, too small or too large a plasma cleaning parameter, and too small or too large a magnetron sputtering coating parameter will lead to an increase in the corrosion rate of the refractory material and a decrease in thermal shock resistance. Therefore, in comprehensive comparison, the parameter effect of Example 2 is relatively better.
[0110] 3. Investigate the influence of refractory preparation parameters on the corrosion rate and thermal shock resistance of refractory materials.
[0111] The difference between Comparative Example 3 and Example 2 is that in step S1, all raw materials are mixed;
[0112] The difference between Comparative Example 4 and Example 2 is that the third mixed material is integrally pressed and formed;
[0113] Depend on Figure 5 and Figure 6 The results show that some components in the corrosion-resistant microcapsules are easily oxidized or react with other substances to lose their activity. Therefore, the present application mixes them with refractory aggregates under a nitrogen atmosphere to avoid contact with oxygen and other substances that may cause deterioration, and better maintain their corrosion resistance and other characteristics. The use of microwaves to rapidly heat the inside of the material produces strong molecular motion and stirring effects, which can effectively break up agglomerates and evenly disperse hafnium nitride particles in the refractory aggregate. Therefore, the present application conducts step-by-step mixing based on the properties of corrosion-resistant microcapsules and hafnium nitride, which can improve the bonding degree and density of each raw material powder, so In Control Example 3, when all raw materials are mixed at one time, the corrosion-resistant microcapsules, hafnium nitride and refractory aggregates may interfere with each other, affecting the performance of their respective properties; while the present application divides the refractory material into a multi-layer structure coated sequentially from the inside to the outside, so that the particle distribution inside the material is more uniform, and the density difference of each part is reduced, which helps to improve the overall strength and stability of the refractory material. Therefore, the refractory material structure of the overall pressed molded refractory material of Control Example 4 is single, lacking the mutual support of the multi-layer coating. Therefore, Control Examples 3 and 4 significantly increase the corrosion rate of the refractory material and significantly reduce the thermal shock resistance compared with Examples 2 and 21 to 32;
[0114] By comparing Examples 2 and 21 to 32, it can be seen that the proportion of silicon dioxide and the like in the first mixture is too small or too large, the mixing parameters of the first mixture are too small or too large, the microwave parameters of the second mixture are too small or too large, the mass proportion of the center layer in the third mixture is too small or too large, the mass ratio of the next layer to the previous layer is too small or too large, and the high-temperature firing parameters are too small, which will lead to an increase in the corrosion rate of the refractory material and a decrease in the thermal shock resistance. In Example 32, the high-temperature firing parameters are larger and the corrosion rate is smaller, but the thermal shock resistance is almost the same as that of Example 2, and the reduction in the corrosion rate is smaller. Therefore, from an economic point of view, the parameter effect of Example 2 is relatively better.
Claims
1. A corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln, characterized in that: Calculated by mass percentage, it includes the following components: Silicon dioxide: 8-10%; Alumina: 5-7%; Mullite: 20-30%; Hafnium nitride: 0.3-0.5%; Corrosion-resistant microcapsules: 0.1-0.3%; Binder: 3-5%; Corundum: remainder.
2. The corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to claim 1, characterized in that: The preparation method of the corrosion-resistant microcapsules is: Dispersing polyvinyl alcohol and pentaerythritol in deionized water at a mass ratio of 1:0.5:40-50, and adjusting the pH to 7-9 to obtain an aqueous phase solution; mixing and ultrasonically dispersing the modified glaze, aluminum oxide powder with a particle size of ≤2 μm, an emulsifier, and aluminum dihydrogen phosphate solution with a mass concentration of 40-50% at a mass ratio of 1:1.5:0.2-0.8:0.5 to obtain an oil phase solution; The oil phase solution and the water phase solution are mixed and emulsified in a mass ratio of 2 to 3:7, the mixing speed is 4000 to 5000 r / min, the heating temperature is 25 to 45° C., and the emulsification time is 10 to 15 minutes to obtain an emulsion; flame-retardant viscose fibers are added to the emulsion in a mass ratio of 1:0.02 to 0.04, the temperature is raised to 65 to 75° C. in a nitrogen atmosphere, and the mixture is stirred for 2 to 3 hours, and then vacuum dried at -15 to -5° C. for 10 to 12 hours to obtain corrosion-resistant microcapsules with a particle size of 25 to 45 μm.
3. The corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to claim 2, characterized in that: The preparation method of the modified glaze is: The glaze and 1-naphthalenecarboxylic acid are ultrasonically dispersed in methanol at a mass ratio of 4:1:20-25, and then centrifugally washed and dried to obtain a modified glaze intermediate; After the modified glaze intermediate is plasma cleaned, a TiC film is magnetron sputtered on the surface of the modified glaze intermediate, argon is used as the protective gas, nitrogen is used as the reaction gas, the coating working pressure is 0.6-0.8 Pa, the titanium target sputtering power is 120-180 W, the argon flow rate is 32-38 mL / min, the nitrogen flow rate is 1.5-2.5 mL / min, the sputtering temperature is 420-480° C., and the magnetron sputtering coating treatment time is 40-50 min to obtain a modified glaze.
4. The corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to claim 3, characterized in that: The glaze is selected from any one of zircon powder, kyanite powder and feldspar powder.
5. The corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to claim 3, characterized in that: The power of the plasma cleaning is 350-450W, and the cleaning time is 5-10 minutes.
6. The corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to claim 1, characterized in that: The emulsifier is Span80.
7. The corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to claim 1, characterized in that: The binder includes any one or more of cement, silicate and aluminate.
8. The corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to claim 1, characterized in that: The particle size of the silicon dioxide is 40-70 nm, the particle size of the aluminum oxide is ≤5 mm, the particle size of the mullite is 1-3 mm, and the particle size of the corundum includes three types of 1-3 mm, 0.088-1 mm, and 0-0.088 mm with a mass ratio of 1:1.5-2:1.
5.
9. The method for preparing a corrosion-resistant silicon-aluminum refractory material for hazardous waste rotary kiln according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix silicon dioxide, aluminum oxide, mullite and corundum uniformly and divide them into mixture A and mixture B with a mass ratio of 1 to 3:1; first, stir and mix mixture A and corrosion-resistant microcapsules in a nitrogen atmosphere for 20 to 30 minutes, with a nitrogen introduction rate of 0.1 to 0.3 L / min, to obtain a first mixture; S2, stirring and mixing the mixture B and hafnium nitride under the action of microwave, the microwave power is 400-600W, the time is 5-10min, to obtain a second mixture; S3, stirring and mixing the first mixed material obtained in step S1, the second mixed material obtained in step S2, and the binder for 15 to 25 minutes to obtain a third mixed material; S4, 15-20% of the third mixture obtained in step S3 is used as W1, and pre-pressed at 120-130 MPa as the center layer, and the remaining third mixture is divided into n portions, and the mass of each portion of the third mixture is W n , then W n =2~2.5W n-1 , n>1, n portions of the third mixed material are used to wrap the previous layer in turn, and then pre-pressed at 120-130 MPa to obtain a new layer, and the length, width and height ratios of each layer are equal to obtain a blank; S5. The blank of step S4 is then fired at a high temperature of 1250-1350° C. for 10-12 hours to obtain a silicon-aluminum refractory material.